Aplikasi Kulit Nanas (Ananas comosus L. Merr) Fermentasi dalam Ransum untuk Menunjang Produktivitas Ayam Joper (jawa Super) Fase Finisher - S Abadi; A A Candra; Z Zairiful (PETERPAN (Jurnal Peternakan Terapan), 2022)
Joper chicken is a poultry the result of a cross between a rooster and a purebred chicken.  The research of this study was to analyze the effect of using fermented pineapple skin flour (Ananas comosus (L). Merr) in rations on the productivity of joper chicken in the finisher phase.  The study was conducted on 90 joper chickens from the age of 1 day (DOC) to the age of 65 days.    This research used a paired sample t test with 2 treatments and 15 replications, the treatments were P0 (control ration of 0% TKNF), and P1 (ration added 10% of TKNF).  The data obtained from the study were calculated using Microsoft Excel and analyzed using SPSS. The results of the study showed that the use of fermented pineapple peel flour did not have a significant effect (P>0.05) on the observed parameters. the parameters analyzed were ration consumption, PBT, FCR, and IOFCC. The results showed that the P0 and P1 treatments were ration consumption of 1.860 g/head and 1.877 g/head, PBT of 688 g/head and 697 g/head, FCR of 2.70 and 2.69, and IOFCC of Rp. 14.787.00 and Rp. 15.731.00.